Simulation of patient-specific brain deformation due to brain shift - Subramaniam, S.R.; Loncaric, S.; Schulder, M. (29th Annual Northeast Bioengineering, 2003)
Surgical navigation systems require display of pre-operative and intra-operative data in the same coordinate system. This requires a registration of preoperative image data and intra-operative magnetic resonance (MR) image data. The registration problem is difficult because of the brain shift effect. Brain shift is caused by surgical intervention, and by medications received by the patient. In order to achieve an accurate registration it is necessary to use an elastic registration method. The main idea of this work is to guide an elastic registration method using biomechanical modeling of the brain shift effect. This will allow for a faster and more accurate registration of pre-operative and intraoperative MR images. The goal of the present work is to develop a framework for the full-scale, real time, finite element simulation of patient specific elastic tissue deformation in brain due to brain shift. In this paper, we present initial work on simulation of a patient specific virtual model of brain deformation due to brain shift.